Pendekatan Preemtif dan Preventif dalam Penanganan Gangguan Keamanan dan Ketertiban oleh Bhabinkamtibmas Kelurahan Banguntapan - Joko Tri Hasbiyanto; Sri Widayanti (Jurnal Sociohumaniora Kodepena (JSK), 2026)
This study examines the preemptive and preventive approaches implemented by Bhabinkamtibmas (Community Security Officers) of Banguntapan Village, Bantul Regency, in handling community security and order disturbances. Banguntapan is the most densely populated sub-district in Banguntapan District and recorded the second-highest number of criminal cases in Bantul in 2024. Design/methodology/approach: This study employs a descriptive qualitative method, collecting data through interviews, observations, and documentation from seven informants. Findings: Findings reveal that preemptive measures include community counseling, establishment of neighborhood watch posts (Poskamling), and dissemination of public advisories; while preventive measures encompass routine patrols, surveillance of crime-prone areas, and community relationship-building. Both approaches yield positive outcomes including increased legal awareness, community participation in neighborhood security activities, and a reduction in security disturbances. Key obstacles include insufficient public trust and a tendency to conceal problems. Originality/value/limitations of the study: This study recommends strengthening Bhabinkamtibmas capacity and enhancing synergy among community elements.